Optimizing of Arabica Coffee Bean Fermentation Process Using a Controlled Fermentor - Sukrisno Widyotomo; Yusianto Yusi (Indonesian Coffee and Cocoa Research Institute, 2013)
One of primary coffee processing steps which affect the end quality isfermentation. Fermentation using a controlled fermentor might be usefulbecause all of parameters which influence coffee quality can be controlled.The aim of this research is to evaluate performance of controlled fermentor forfermentation process of Arabica coffee beans. Main material of this researchwas ripe Arabica coffee cherries from Andungsari Research Station in Bondowoso district. Research parameters were temperature with four levels i.e.: ambient temperature, 30o C, 35oC and 40oC, and fermentation time with three levels i.e.: 6 hours, 12 hours, and 18 hours. A horizontal type of modified fermentor has been tested with 20 kg/batch or 50% of maximum loading capacity. The result showed that an electric heater as energy source can raise temperature duringfermentation process. Fermentation process using fermentor at 30-40oC had not significant effect on physical properties change such as density, beancount per 100 g and distribution of beans. Optimum condition for Arabica fermentation process in a modified fermentor reactor was 25oC temperature, and 12 hours fermentation time. By this condition, green beans have good organoleptic score than other fermentation process treatments. Key words: Fermentor, fermentation, coffee, quality, organoleptic, horizontal cylinder.